Pengaruh Buah Pepaya pada Remaja Putri yang Mengalami Anemia terhadap Peningkatan Hemoglobin di Wilayah Kerja Puskesmas Kampung Jabi Kota Batam - Suci Jessica Berkati Marpaung; Mona Rahayu Putri; Didi Yunaspi (Pusat riset dan Inovasi Nasional, 2025)
Globally, 33% of all productive women aged 15-49 have anemia problems. Anemia is a condition where there is a deficit of erythrocyte cells, which is often found in all age groups, including women of childbearing age (WUS) and young women, namely 29% of young women and non-pregnant women and 38% of pregnant women have problems with anemia. This research aims to determine the effect of giving papaya fruit to young women who suffer from anemia on increasing hemoglobin in the work area of the Jabi Village Community Health Center, Batam City in 2024. This research was conducted using the Pre-Experiment method using the One Group Pretest Posttest Design approach. The sample for this research was 16 young women. The results of this study showed that the majority of young women experienced moderate anemia, as many as 10 young women (62.5%). After giving papaya to young women for 10 days, it was found that the majority of young women were not anemic, as many as 10 young women (62.5%). Based on the results of the Paired Sample T Test statistical test, show that the p-value is 0.000 < 0.05, so it can be concluded that there is an effect of giving papaya fruit to young women who experience anemia on increasing hemoglobin in the working area of the Jabi Village Community Health Center, Batam City in 2024. It is hoped that the Health workforce can minimize anemia in young women by giving them papaya.